PERILAKU PETANI DALAM USAHATANI MANGGA DI KABUPATEN CIREBON - Rani Andriani Budi Kusumo; Elly Rasmikayati; Gema Wibawa Mukti (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2018)
As one of the largest mango producers in the world, there are still problems faced by farmers in terms of product quality and productivity. The quantity and quality of mango produced by farmers is influenced by the behavior of mango farmers in their farming activities. This research were aimed to analyze: 1) farmers perception of mango farming in Cirebon Regency; 2) behavior of farmers in mango farming in Cirebon Regency; 3) Factors related to farmer behavior in mango farming in Cirebon Regency. The research was conducted by survey-explanatory method. Respondents in this study were 130 mango farmers who were taken at random by multi-stage random sampling technique. Descriptive statistical analysis and Spearman rank correlation analysis were used to answer the research objectives. The result of analysis showed that most farmers have not applied fertilization technique, the use of growth regulators and pest management as recommended. Price stability was a factor associated with farmer behavior in various activities of his farming. Efforts were needed to ensure price stability received by farmers so that farmers are more motivated to improve productivity and yield quality.Keywords: mango, behavior, farmers, farming